Artificial intelligence and human rights: a comprehensive study from Indian legal and policy perspective. Issue 1 (17th June 2021) - Chatterjee, Sheshadri; N.S., Sreenivasulu
Abstract : Purpose: The purpose of this study is to investigate the impact of artificial intelligence (AI) on the human rights issue. This study has also examined issues with AI for business and its civil and criminal liability. This study has provided inputs to the policymakers and government authorities to overcome different challenges. Design/methodology/approach: This study has analysed different international and Indian laws on human rights issues and the impacts of these laws to protect the human rights of the individual, which could be under threat due to the advancement of AI technology. This study has used descriptive doctrinal legal research methods to examine and understand the insights of existing laws and regulations in India to protect human rights and how these laws could be further developed to protect human rights under the Indian jurisprudence, which is under threat due to rapid advancement of AI-related technology. Findings: The study provides a comprehensive insight on the influence of AI on human rights issues and the existing laws in India. The study also shows different policy initiatives by the Government of India to regulate AI. Research limitations/implications: The study highlights some of the key policy recommendations helpful to regulate AI. Moreover, this study provides inputs to the regulatory authorities and legal fraternity to draft a much-needed comprehensive policy to regulate AI in the context of the protection of human rights of the citizens. Originality/value: AI is constantly posing entangled challenges to human rights. There is no comprehensive study, which investigated the emergence of AI and its influence on human rights issues, especially from the Indian legal perspective. So there is a research gap. This study provides a unique insight of the emergence of AI applications and its influence on human rights issues and provides inputs to the policymaker to help them to draft an effective regulation on AI to protect the human rights of Indian citizens. Thus, this study is considered a unique study that adds value towards the overall literature.